Engineered Wood Products for Construction (IntechOpen, 2022)
Wood is a gift from nature. It is a sustainable and renewable bio-composite material that possesses a natural ability to mitigate carbon dioxide. However, due to deforestation and climate change, it has become necessary to develop alternative building and construction materials. Engineered wood products (EWPs) such as parallel strand lumber, laminated veneer lumber, and cross-laminated timber are promising substitutions for conventional lumber products. This book presents a comprehensive overview of EWPs, including information on their classification, design, synthesis, properties, and more. It is divided into two sections: “General Overviews and Applications of EWPs” and “Recent Research and Development of EWPs”. The book is a valuable reference for manufacturers, engineers, architects, builders, researchers, and students in the field of construction.